SA says no to aid cuts: Interview with Zackie Achmat - Levy, Moira (New Agenda: SA Journal of Social and Economic Policy, 2025)
Amid the havoc wreaked in South Africa’s health sector by Donald Trump’s guillotining of the United States’ international aid programme, Zackie Achmat reminds us that the earliest action against the HIV and AIDS epidemic started as an international grassroots movement that mobilised support from the wealthiest countries. He spoke to Moira Levy about the lessons learned from active citizen engagement in decision-making, especially in the context of the current emergency.